Bananas and Their Wild Relatives in Pandeglang, Indonesia - Susilawati Dewi; Fajarudin Ahmad; Rida Oktorida Khastini; Suroso Mukti Leksono; Nani Maryani (HAYATI Journal of Biosciences, 2023)
Pandeglang is one of the banana producer regencies of Banten, Indonesia, that produce 924 tons per year. However, information regarding the diversity of banana germplasm in this region is unavailable. This study explored districts Cadasari, Banjar, Jiput, Labuan, and Menes. Morphological characters were noted and used to identify the cultivars, subspecies, or varieties. In total, 22 accessions were collected from 22 collection sites. Based on morphological characters, we described 14 banana accessions of 10 cultivars, three accessions of wild Musa acuminata and one of Musa balbisiana. Considering its genome composition, five genome types we described among these banana cultivars, i.e., AA (divided into AA and AA wild), BB, AAA, AAB, and ABB. In this study, we did a principal component analysis and saw that AA wild and AAB were clearly separated, but the other genome types were clustered partially or included in one cluster. Our study expands the information on banana diversity in Indonesia. Further study on the potential of this banana germplasm to be used as a genetic resource to find resistance to banana diseases is needed.